2014
DOI: 10.1890/13-2000.1
|View full text |Cite
|
Sign up to set email alerts
|

Food predictability determines space use of endangered vultures: implications for management of supplementary feeding

Abstract: 16Understanding space use of free-living endangered animals is key to inform management 17 decisions for conservation planning. Like most scavengers, vultures have evolved under a 18 context of unpredictability of food resources (i.e. exploiting scattered carcasses that are 19 intermittently available). However, the role of predictable sources of food in shaping spatial 20 ecology of vultures has seldom been studied in detail. Here, we quantify the home range of the 21Egyptian vulture (Neophron percnopterus), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 57 publications
4
73
3
Order By: Relevance
“…This is especially the case for those populations that now depend on supplementary feeding stations. While foraging patterns of certain species appear to be unaltered by the availability of food at feeding stations [5659], for other species, movements are clearly conditioned, either pushing individuals to take longer forays to feed on supplementary stations [60] or restrict food searching to those places [61]. The high abundance of alternative food sources and diet plasticity of certain populations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially the case for those populations that now depend on supplementary feeding stations. While foraging patterns of certain species appear to be unaltered by the availability of food at feeding stations [5659], for other species, movements are clearly conditioned, either pushing individuals to take longer forays to feed on supplementary stations [60] or restrict food searching to those places [61]. The high abundance of alternative food sources and diet plasticity of certain populations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Using the same birds, the latter authors reported home range sizes (according to MCP) ranging from 45.42 km 2 to 142.66 km 2 (51.30-142.66 km 2 for males and from 45.42 to 134.84 km 2 for females) (Martínez et al 2011). These differences in home range size can be logically accounted for the different tracking methods, indicating that radiotracking tends to underestimate measures of home range size in comparison with unbiased GPS satellite tracking technologies (Girard et al 2002;e.g., García-Ripollés et al 2011;López-López et al 2014a). With regards to sex differences in ranging behaviour, previous studies suggested different levels of space use by males and females, with females tending to range across larger areas than males, particularly during the pre-laying and pre-migratory periods (Díaz-Ruiz and Cebollada-Baratas 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Following similar studies focused on the analysis of spatio-temporal variations in home range behaviour of long-lived territorial raptors (e.g., Campioni et al 2013;López-López et al 2014a), we divided each breeding season into three periods: (1) a ''pre-laying'' period, which spanned from the arrival at breeding areas until egg laying; 2) a ''incubation ? nestling'' period, which comprised an average period of 39 days of incubation (García-Dios 2009) plus the period in which nestlings remained in the nest just before their first flights [52 days on average; García-Dios (2009)]; and finally, a (3) ''pre-migration'' period, including the dependence period of juveniles once fledged until the onset of autumn migration to their wintering grounds.…”
Section: Study Area and Bird Taggingmentioning
confidence: 99%
“…However, ecologically important insect assemblages and other already vulnerable species may be exposed to such residues, with as yet unknown consequences (e.g., the Egyptian vulture, which is coprophagous [179][180] and rapidly declining in some parts of its range [181,182]. Residues of antiparasitic agents (e.g., endectocides like ivermectin) in the dung of livestock animals can be harmful to a number of coprophagous insects [183][184][185][186] that perform similar ecosystem services to vultures, but on a less obvious microscale.…”
Section: Analysis Of Fecal Mattermentioning
confidence: 99%